2011
DOI: 10.1177/1069072711409713
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Evaluation of the Career Decision Self-Efficacy Scale–Short Form Among French University Students

Abstract: The purpose of the present study was to examine the reliability and the factor structure of the Career Decision Self-Efficacy Scale–Short Form (CDSES-SF) among French university students. Based on a sample of 650 respondents, the alpha coefficients indicated high reliability for total scores but not for the subscale scores with values of .70 and below. The test–retest reliability of the total scores was .81. The original and theoretical five-factor model demonstrated inadequate model fit. A four-factor model, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 44 publications
4
24
1
9
Order By: Relevance
“…Previous international studies found that CDSES-SF has a one-factor structure (Jin et al 2012;Miguel et al 2013); whereas, others found that it has a multifactor structure Buyukgoze-Kavas 2014;Chaney et al 2007;Creed et al 2002;Gaudron 2011;Hampton 2005). The original five-factor structure was also replicated before (Makransky et al 2014;Miller et al 2009;Presti et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous international studies found that CDSES-SF has a one-factor structure (Jin et al 2012;Miguel et al 2013); whereas, others found that it has a multifactor structure Buyukgoze-Kavas 2014;Chaney et al 2007;Creed et al 2002;Gaudron 2011;Hampton 2005). The original five-factor structure was also replicated before (Makransky et al 2014;Miller et al 2009;Presti et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, Buyukgoze-Kavas (2014) examined the original structure of which demonstrated less than ideal CFA indices and reliabilities. Moreover, the solution of Gaudron (2011) proved to be adequate in terms of factor structure, but not reliability as two factors were far below the acceptable value. Finally, the original five-factor structure was replicated in American (Miller, Roy, Brown, Thomas, and McDaniel 2009), Australian (Makransky, Rogers, and Creed 2014), and Italian (Presti et al 2013) samples as well.…”
Section: The Dimensionality Of the Cdses-sfmentioning
confidence: 99%
See 1 more Smart Citation
“…Les scores des deux formes sont hautement fidèles. Par exemple, Nilsson, Schmidt et Meek (2002) (Gaudron, 2011 ;Luzzo, 1993 ;Mau, 2000) ont rapporté des coefficients de fidélité testretest élevés, de .81 à .83, pour des intervalles de temps variant de 4 à 6 semaines.…”
Section: Caractéristiques Psychométriques Des éChelles Cdsesunclassified
“…Analisando os escores por sub-escala, ficaram entre 0,53 e 0,91. Alguns artigos também relataram estimativas de precisão pelo método de teste-reteste, com resultados entre 0,81 e 0,83 (Taylor & Betz, 1983;Luzzo, 1993;Peterson & delMas, 1998;Watson et al, 2001;Hampton, 2006;Ramírez & Canto, 2007;Chaney et al, 2007;Silva et al, 2009;Lozano, 2006;Gaudron, 2011).…”
Section: Aplicação Da Autoeficácia No Contexto Do Desenvolvimento De unclassified